Penerapan Automatic Weather Station Dalam Pemetaan Kecepatan Angin dan Arah Angin Sebagai Dasar Perancangan Turbin Angin - Nurdin, Akhmad; Munadi, Muhammad; Sidiq, Rustam (Infotekmesin, 2022)
The use of Small Wind Turbine (SWT) technology is currently being developed in residential and urban areas. The application of SWT can be directly integrated into a building called the Building Integrated Wind Turbine and the industrial area is one area that has the potential to develop the SWT concept as a Building Integrated Wind Turbine. Before designing and manufacturing a wind turbine for a Building Integrated Wind Turbine, data on wind density and direction is required. In areas where wind speed and direction have not been recorded, it is necessary to study wind velocity and direction data in real-time and in real conditions for a certain period. This study aims to map wind density and wind direction with real-time properties in the foundry industry area, Ceper District, Klaten Regency, so the potential value and value of wind density energy can be known. This research method includes data retrieval carried out in real time and in real conditions using the Automatic Weather Station instrument which was carried out from August 6 to September 6, 2021. The data obtained were random data and processed using weibull distribution statistics with Microsoft Excel software. The results of this study indicate an average wind speed of 2,038 m/s in stable conditions and sufficient wind gusts with a power density value of 6,994 Watt/m2. The wind direction tends to be south-east after the wind gusts are hampered by the building profil.